Jumlah semut Myopopone castaneae (Hymenoptera:Formicidae) yang dihasilkan dengan pakan berbagai instar larva Oryctes rhinoceros L. (Coleoptera: Scarabaidae) di laboratorium - Irena Santy Waruwu; Marheni; Lahmuddin Lubis (Jurnal Pertanian Tropik, 2018)
Ants of Myopopone castaneae (Hymenoptera: Formicidae) is a one potential predators of larvae palm stem borer Oryctes rhinoceros L. (Coleoptera: Scarabidae). These ants are able to prey on all stadia of larvae O. rhinoceros L. This research was aimed to know the number of ants Myopopone castaneae (Hymenoptera: Formicidae) generated by feeding the various instar larvae of palm stem borer Oryctes rhinoceros L. (Coleoptera: Scarabaidae) in the laboratory. The research was conducted at Laboratory of Plant Pest, Faculty of Agriculture, University of Sumatera Utara from April until September 2017. This research used nonfactorial Randomize Completely Design with 3 treatments and 6 replications. The results showed that various instar larvae O. rhinoceros was significantly different to number of ants generated. The highest number of ants was instar I (0,67 queen ants, 2,17 male ants, and 68 working ants) dan the lowest number of ants was instar III (0 queen ant, 0 male ant and 65,83 working ant). The highest consumption was instar I (130,17 ants) and lowest one was instar III (73,83 ants). There were three types of ants in colony including queen, male and working ants.